2021
DOI: 10.3390/app11188290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soft Computing Techniques for the Prediction of Suspended Sediment Loads in Rivers

Abstract: A key goal of sediment management is the quantification of suspended sediment load (SSL) in rivers. This research focused on a comparison of different means of suspended sediment estimation in rivers. This includes sediment rating curves (SRC) and soft computing techniques, i.e., local linear regression (LLR), artificial neural networks (ANN) and the wavelet-cum-ANN (WANN) method. Then, different techniques were applied to predict daily SSL at the Pirna and Magdeburg Stations of the Elbe River in Germany. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Additional analyses of streamflow data could include a time‐since‐last‐event feature that could teach the model sediment source and storage controls to help better account for hysteresis (Gellis, 2013; Smith & Dragovich, 2009). ML is a complex and ever‐changing field of study; additional work could be done exploring other methods including artificial neural networking (ANN) and, more specifically, hybrid wavelet and neural networking (WANN), which produced accurate results in sediment transport prediction studies (Afan et al, 2016; Khan et al, 2021). Lastly, the models could be improved with additional sites and additional samples to better represent sediment transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional analyses of streamflow data could include a time‐since‐last‐event feature that could teach the model sediment source and storage controls to help better account for hysteresis (Gellis, 2013; Smith & Dragovich, 2009). ML is a complex and ever‐changing field of study; additional work could be done exploring other methods including artificial neural networking (ANN) and, more specifically, hybrid wavelet and neural networking (WANN), which produced accurate results in sediment transport prediction studies (Afan et al, 2016; Khan et al, 2021). Lastly, the models could be improved with additional sites and additional samples to better represent sediment transport.…”
Section: Discussionmentioning
confidence: 99%
“…ML is a complex and ever-changing field of study; additional work could be done exploring other methods including artificial neural networking (ANN) and, more specifically, hybrid wavelet and neural networking (WANN), which produced accurate results in sediment transport prediction studies (Afan et al, 2016;Khan et al, 2021).…”
Section: Possible Model Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as computing and artificial intelligence technology are developing, the artificial neural network has been widely used in mathematical model building and disaster prediction. Artificial intelligence models can be used to predict and cluster various hydrological problems, such as prediction of rainfall, runoff and sediment, in which the most used models are ANN, SVM/SVR, ANFIS, genetic algorithm (GA), particle swarm algorithm (PSO) and artificial bee colony algorithm (ABC) [8][9][10][11]. Based on the hydrological model of ANN, the flow prediction problem with precipitation as an input showed that the wavelet derived value can provide relevant flow path and hydrological information [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya et al [18] performed comparative evaluation using an ANN and a model trees method for the estimation of sediment yield. Khan et al [19] employed ANN and wavelet-cum-ANN methods to estimate suspended sediment loads in the Elbe River in Germany. In addition, Nhu et al [20] presented erosion susceptibility mapping through the development of a hybrid model that simultaneously utilized various data mining techniques.…”
Section: Introductionmentioning
confidence: 99%